Combination Image Analysis of Tongue Color and Sublingual Vein Improves the Diagnostic Accuracy of Oketsu (Blood Stasis) in Kampo Medicine - Morita, Akira; Murakami, Aya; Noguchi, Keigo; Watanabe, Yuki; Nakaguchi, Toshiya; Ochi, Sadayuki; Okudaira, Kazuho; Hirasaki, Yoshiro; Namiki, Takao (Frontiers in Medicine, 2022)
Aim: In tongue diagnosis, the dark purple tongue and the sublingual vein are important findings of blood stasis. However, the association between the tongue color and the sublingual vein has not been reported. This study investigated the association between the tongue body color and the sublingual vein width using tongue image analyzing system (TIAS) for the objective assessment of Oketsu (blood stasis). Methods: Thirty-eight patients (age 68.7±11.3 years, 14 men and 24 women) who visited the Department of Kampo Medicine at Chiba University Hospital were included. The physical findings, blood test results, blood stasis score from medical records, and tongue images obtained with TIAS were extracted. The patients were classified into two groups: a sublingual vein width of ≤2.5 mm (20 patients) and a sublingual vein width of >2.5 mm (18 patients). Results: The color values significantly related to the sublingual vein width (mm) are the b* (blueness: tongue edge and tongue posterior) and the L* (darkness: tongue edge and tongue apex). The area under the curve was greater for the combination of the tongue body color and the sublingual vein width than that for either of them. Conclusion: This study showed the findings of the objective evaluation of blood stasis of the tongue in patients with a dark-blueness tongue and an enlarged sublingual vein. In addition, the combination of the tongue body color and the sublingual vein width is expected to facilitate a more reliable diagnosis of blood stasis.